Human Immunodeficiency Virus-Negative Men Who Have Sex With Men Have an Altered T-Cell Phenotype and Bioenergy Metabolism - Kruize, Zita (Open Forum Infect Dis, 2020)
BACKGROUND: We recently reported that the levels of activation, exhaustion, and terminal differentiation within the peripheral T-cell compartment were increased in men who have sex with men (MSM) compared with blood bank donors. During activation and differentiation, T cells undergo metabolic changes to maintain their energy demand. METHODS: The effect of cytomeglovirus (CMV) infection and risk behavior on the immune phenotype of peripheral T cells and the immune bioenergy metabolism profile in human immunodeficiency virus-negative MSM (with high or low sexual risk behavior) and blood bank donors was evaluated. RESULTS: Men who have sex with men exhibited increased levels of T-cell activation and terminal differentiation and an impairment of the bioenergy metabolism (mitochondrial respiration and glycolysis) compared with blood bank donors. Cytomeglovirus infection was associated with increased terminal differentiation of CD4(+) (B = 3.41; 95% confidence interval [CI], 1.98–4.85; P < .0001) and CD8(+) T cells (CD57(+): B = 1.21, 95% CI = 0.41–2.02, P = .004; CD27(−)CD28(−): B = 2.20, 95% CI = 1.21–3.18, P < .0001; and CD57(+) of CD28(−): B = 1.02, 95% CI = 0.38–1.66, P = .002) and increased glycolysis (B = 0.97; 95% CI, 0.27–1.67; P = .007). Risk behavior was associated with increase activation of CD4(+) T cells (B = 0.22; 95% CI, 0.07–0.37; P = .005), increased terminal differentiation of CD4(+) (B = 0.82; 95% CI, 0.44–1.20; P < .0001) and CD8(+) T cells (B = 1.55; 95% CI, 0.58–2.51; P = .002), and decreased glycolysis (glycolysis: B = −0.40, 95% CI = −0.68 to 0.12, P = .006; and glycolytic capacity: B = −0.54, 95% CI = −0.91 to 0.16, P = .005). CONCLUSIONS: Men who have sex with men show an increased prevalence of bloodborne and sexually transmitted infection, indicating that immunological changes in the T-cell population and the bioenergy metabolism observed in MSM can most likely be attributed to chronic antigen exposure.